If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14x + 3(2x + -5) = -19 + -7x Reorder the terms: -14x + 3(-5 + 2x) = -19 + -7x -14x + (-5 * 3 + 2x * 3) = -19 + -7x -14x + (-15 + 6x) = -19 + -7x Reorder the terms: -15 + -14x + 6x = -19 + -7x Combine like terms: -14x + 6x = -8x -15 + -8x = -19 + -7x Solving -15 + -8x = -19 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -15 + -8x + 7x = -19 + -7x + 7x Combine like terms: -8x + 7x = -1x -15 + -1x = -19 + -7x + 7x Combine like terms: -7x + 7x = 0 -15 + -1x = -19 + 0 -15 + -1x = -19 Add '15' to each side of the equation. -15 + 15 + -1x = -19 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = -19 + 15 -1x = -19 + 15 Combine like terms: -19 + 15 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 4x-20=6x-40 | | 0.3x+0.5=-1.3 | | 3(n-5)=.4-.2(n-7) | | 2y+4=2x | | -12x^2-144x-216=0 | | 32-7x=14+11x | | 44+3x=(X+20) | | 78=5y | | 6x-7=3x+4 | | 6(x-6.5)=9.6 | | 0.2x=0.3 | | 19-4(x+4)=11(x+2)-1 | | 2+(-5)(h+3)=-28 | | -4y+4x=12 | | -3d=13 | | 2+(-5)(h+3)=28 | | y=10000+1x | | 4z-5z+6= | | 9(8x-9)=-351 | | -3y+2y+5=12 | | -4+3c+6=2c+2+c | | 2(x-5)+7=6x-4(1+x) | | 8(c-2)+4=3+c-15 | | 4x+6.46=2x+10 | | x^2-30x-63=0 | | 0.2x+0.1=0.12-0.06 | | 2x-17=14x+1 | | 10x-7=3x+8 | | 6x-(2x+8)=3x+(x+6) | | y=0-5x | | 500=55n-35n | | 4(n+4)=-2(4+2n) |